Literary stylistics and translation / Dan Shen - Shen, Dan1958-
At head of title: Huo di er jie quan guo qing nian you xiu she hui ke xue cheng guo zhuan zhu jiang. Based on the author's Ph. D. thesis, University of Edinburgh.